The role of professional licensing in developing the performance of general education teachers in the Kingdom of Saudi Arabia: opportunities and challenges - Alrifai, Samia Abdulrahman (Journal of Educational and Psychological Sciences, 2025)
This research aimed to identify the role of the professional license in enhancing the performance of general education teachers in the Kingdom of Saudi Arabia, as well as the main opportunities and challenges that teachers face in obtaining the professional license. The study employs a descriptive methodology with an analytical approach to the reality of the professional license, along with a critical review of the literature, studies, and global experiences that have addressed the professional license from this perspective. The research reached several conclusions, the most important of which are: 1-The professional license contributes to enhancing teachers' commitment to professional values and responsibilities, developing their knowledge of their specialization and teaching methods, and improving their professional practices, which raises the quality of education.2-The professional license provides opportunities for continuous professional growth and fosters positive competition among teachers, motivating them to develop their skills and improve their teaching performance.3-The professional license faces challenges such as the difficulty of passing the tests, time constraints, and a lack of training opportunities, which necessitates the provision of additional support and effective qualification programs.The research recommends raising awareness of the importance of the professional license in developing teachers' performance, focusing on the professional qualification program to prepare teachers for obtaining the license, incorporating a performance aspect that is currently lacking in the license, and not limiting it.
Keywords: teacher performance development; challenges; opportunities; professional license